Dženderizam novi oblik totalitarizma - Poljaković, Ivan, filolog (2021)
Dženderizam je novonastajući koncept koji se odnosi na glavnostrujašku politiku koja nameće pozitivan pogled na kulturu smrti kao što su kontracepcija, pobačaj i rodna ideologija. Prezentiran je kratak opis uzroka i razvoja ovog novog totalitarizma kao i njegove posebnosti. Njegovo širenje nastalo je u tri faze: seksualna revolucija, pravo na pobačaj i rodna teorija. Ustvrđeno je da će dženderizam, iako s potpuno drugačijim alatima i karakteristikama u odnosu na prijašnje totalitarizme, ipak imati, i već ima, razorne posljedice na društvo u cjelini. Ovaj rad podastire dokaze za smrtna ishodišta prouzročena širenjem dženderizma i upozorava na njegov golem udarac u budućnosti, ne samo na individue nego i na narode kao takve.
Genderism is a new emerging concept referring to the mainstream political agenda that imposes a positive view on the culture of death, such as contraception, abortion and gender ideology. A brief description of the cause and development of this new totalitarianism is given, as well as its particular features. Its expansion incurred in three phases: the sexual revolution, the right to abortion, and gender theory. It has been asserted that genderism, albeit with totally different tools and characteristics than previous totalitarianisms, will have and already has destructive consequences for society as a whole. This paper submits evidence for the lethal outcomes caused by the spread of genderism and warns against its huge impact in the future, not only for individuals, but for nations as well.
Bibliografske bilješke uz tekst.
Sažetak ; Summary.
Keywords: Dženderizam -- Kultura smrti -- Kontracepcija -- Pobačaj -- Rodna teorija